Effect of carbonaceous reinforcements on the mechanical and tribological properties of friction stir processed Al6061 alloy. (15th May 2016) - Maurya, Rita; Kumar, Binit; Ariharan, S.; Ramkumar, J.; Balani, Kantesh
Abstract: Aluminum alloy (Al6061) is an eminent aerospace and automotive material, but its poor wear-resistance can be circumvented by friction stir process (FSP) via microstructural modification. Herein, carbonaceous particles (graphite, carbon nanotubes and graphene) are reinforced in order to assess their effect on mechanical and tribological properties of FSP Al6061. Raman spectroscopy has indicated the retention of damaged carbonaceous product in the stir zone due the intense plastic deformation and shear stresses involved in the FSP. Damage of carbonaceous particles was further confirmed from the transmission electron microscopy. Surface peak-hardness was observed to increase ( 1.3 GPa) for graphene reinforced composite when compared to that of untreated Al6061 ( 0.5 GPa) due to grain refinement (50–100 nm). A substantial reduction in Hertzian-contact-diameter from 117 μm in unprocessed Al6061 alloy to 103 μm upon graphene reinforcement, has ensued least wear volume (0.03 × 10 − 3 mm 3 ) compared to that of untreated Al6061 alloy ( 0.1903 × 10 − 3 mm 3 ). Self-lubricating nature of carbonaceous material has indicated lower frictional force and dominance of gross-slip regime with graphene reinforcement in FSP Al6061 when compared to that of stick-slip wear damage in untreated Al6061. Graphical abstract: Highlights: Friction stir processing (FSP) of Al-6061 alloy with graphite, CNT and graphene reinforcement Evaluation of tribological performance with carbonaceous reinforcement Friction-log plot via fretting of the carbon-reinforced friction stir processed Al6061 Role of tribo-oxidation in enhancing the COF during fretting Damage resistance with graphene reinforcement in friction stir processed Al-6061